Nilai - nilai pendidikan karakter bagi anak usia dini (telaah terhadap QS. Luqman 12-19 dalam tafsir Al Misbah) - Hilda Putri Seviarica; Difaul Husna; Anaas Tri Ridlo Dina Yuliana (At Turots: Jurnal Pendidikan Islam, 2023)
Education is not only to transfer knowledge but also to internalize character values in life. In line with this, Islam strongly emphasizes the importance of having a noble character as a result of the process of cultivating education. Therefore, character education also needs to refer to the Quran, not only science or the fatwas of experts. This literature study aims to explore the value of character values contained in Qs. Luqman verses 12–19 Data collection techniques use document review techniques with primary QS data sources. Luqman from verses 12–19 in Tafsir Al-Misbah. Data analysis in this study used content analysis techniques and comparative methods. Based on the results of the study, it can be concluded that the values of character education in early childhood are contained in QS. Luqman verses 12–19 based on the book of Tafsir Al-Misbah, including gratitude, tawhid, filial piety towards parents, amar ma'ruf nahi munkar, and good morals.